Interleukin-12 encoded by the oncolytic virus VSV-GP enhances therapeutic antitumor efficacy by inducing CD8+ T-cell responses with a long-lived effector cell phenotype - Janine Kimpel; Dorothee von Laer; Theresa Schwaiger; Guido Wollmann; Jasmin Hatami; Krishna Das; Leonie Wolf; Andreas Aufschnaiter; Tobias Nolden; Liesa-Marie Schreiber; Brigitte Müllauer; Elke Podgorschek; et al. (Journal for ImmunoTherapy of Cancer)
Background Vesicular stomatitis virus (VSV) pseudotyped with the glycoprotein (GP) of the lymphocytic choriomeningitis virus (VSV-GP) represents a potent oncolytic virus (OV). Oncolytic virotherapy is an emerging anticancer approach that uses viruses to eliminate cancer cells by direct cell lysis and induction of an antitumor immune response. Immunomodulatory cargos expressed by OVs hold the potential to further enhance this antitumor immune response.Methods To evaluate interleukin-12 (IL-12) as an immunomodulatory cargo encoded by VSV-GP, we used a subcutaneous tumor model by mixing type I interferon (IFN) competent murine lung epithelial cells (TC-1), which are largely resistant to VSV-GP in vivo, with VSV-GP permissive IFN-α receptor knockout TC-1 cells (TC-1ifnar1−/−).Results This mixed model supports prolonged viral replication and subsequent IL-12 production. Oncolytic virotherapy with VSV-GP and VSV-GP-IL12 of parental TC-1 tumors did not lead to tumor control, whereas virus treatment in the TC-1/TC-1ifnar1−/− mixed tumors showed prolonged survival. Furthermore, VSV-GP-IL12 was even more effective than VSV-GP treatment. Analysis of CD8+ T cell responses revealed phenotypic differences of activated CD8+ T cells between VSV-GP and VSV-GP-IL-12 treatment, whereby VSV-GP-IL12-induced CD8+T cells displayed a phenotype described for long-lived effector cells (LLEC). Depletion experiments indicated that CD8+ T cells, and not NK cells, were responsible for the improved efficacy observed with VSV-GP-IL12 treatment.Conclusions Taken together, we have demonstrated that oncolytic virotherapy using VSV-GP encoding IL-12 induces CD8+ T cell responses characterized by an LLEC phenotype, a cell population that is likely a crucial component of antitumor immunity.